Does Governance Make a Difference? - Anderson, G. Lester; Toledo Univ., OH. Center for the Study of Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This document reviews the state of governance. The need for governance based on a process of social adaptation for organizations and institutions is stressed. However, regardless of the differing mechanism for governance, it is suggested that the central theme of governance does make a difference in defining and maintaining the fundamental goals of the higher education system. (MJM)
Educational level discussed: Higher Education.
Critique, v3 n3 p2-4 Jun 1972.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Policy; Educational Administration; Educational Change; Educational Needs; Educational Objectives; Governance; Higher Education; Social Change